SMILING, LAUGHING AND JOKING IN PAPAL ROME: THOMAS OF MARLBOROUGH AND GERALD OF WALES AT THE COURT OF INNOCENT III (1198–1216). (12th February 2018) - Fonnesberg-Schmidt, Iben; Kynan-Wilson, William
Abstract : This article examines textual descriptions of smiling, laughing and joking with the pope in thirteenth-century Rome. It focuses on two Anglo-Norman accounts of conducting litigation at the papal curia: Thomas of Marlborough's (d.1236 ) Chronicon abbatiae de Evesham and Gerald of Wales's (c. 1146–1220×23) De jure et statu Menevensis ecclesiae . Both authors include several careful and prominent references to smiling, laughing and joking, and specifically in relation to Pope Innocent III. These passages have previously been read as straightforward examples of wit and friendship, but this study shows that the authors use these physiological expressions to convey complex and subtly different pictures of the papal curia. Above all, this article demonstrates how Thomas and Gerald's descriptions of humorous interactions with the pope play crucial narrative and mnemonic roles within their work. Abstract : Il presente articolo esamina le descrizioni testuali del sorridere, del ridere e dello scherzare con il Papa nella Roma del XIII secolo. Si focalizza in particolare su due resoconti anglo-normanni di controversie nella curia papale: il Chronicon abbatiae de Evesham di Thomas of Marlborough (data di morte 1236) e il De jure et statu Menevensis ecclesiae di Gerald of Wales (c. 1146–1220×23). In entrambi i testi sono presenti molti riferimenti attenti agli atti di sorridere, di ridere e di scherzare, in particolar modo in relazione a Papa Innocenzo III. Questi passaggi sono stati in precedenza interpretati come inequivocabili esempi di umorismo e amicizia, ma questo studio dimostra come gli autori usino queste 'espressioni fisiologiche' per descrivere immagini leggermente differenti della curia papale. Soprattutto questo articolo mostra come le descrizioni di interazione umoristica con il papa di Thomas of Marlborough e di Gerald of Wales giochino ruoli narrativi e mnemonici cruciali all'interno dei loro lavori.